3 - Épure d’un développement de l’industrie du disque congolaise par le mécénat privé - Léon Tsambu Bulu, (Africa Media Review, 2005)
This article discusses the development of Congo’s music industry through its private sponsorship system. This system is an alternative to the failure of the public system, since the latter has failed to take up the set challenges, after having ruined the colonial heritage that had made Congo a major crossroads for African record music. Congolese records are no longer local cultural products, but have become imported luxury goods. Rather than encouraging people to thinking in terms of essentialist philanthropic sponsorship, culture of showing off, prestige, or even wasting of financial capital, the study invites a reorientation of Congo’s sponsorship resources towards investment (sponsorship entrepreneur) that would help cultural projects for public interest. However, the alternative project will be faced with challenges related to the very nature of the record industry: local and global piracy, which has worsened with the emergence of ICTs, but also challenges related to the low purchasing power of citizens, who are the first ones concerned by such a project; profitability of the domestic market, the tribal nature of the musical space, particularly in Kinshasa, etc. Hence the necessity for the state to get involved in the process of democratisation of culture at a national scale, through incentives such as the setting up of an effective system of protection of copyright, exemption from duty for imported basic infrastructures and exported end products. In a nutshell, it is the state’s responsibility to play its regalian role by implementing an appropriate cultural policy, so that music, better than coltan which is rather putting Congo down, be able to support its economic and social development, just like the Beatles in Great Britain or Bob Marley in Jamaica.